Synergistic Effect of Boric Acid-Urea on the Flame-Retardancy Imparted to Cotton Fabric - Morteza Mostashari, Seyed; Zahra Mostashari, Seyedeh (Asian Journal of Chemistry, 2016)
The synergistic effect between boric acid and urea on the flame-retardancy of cotton fabric (plain construction weighing 168 g/m2) has been of interest in this investigation. The laundered, oven-dried, weighed specimens were impregnated with suitable concentrations of individual aqueous boric acid or urea solutions and some bunches were impregnated with suitable admixed solutions of both chemicals. An acceptable synergistic effect was experienced on applying an admixed bath containing 1.5 M equi-molar solutions of boric acid and urea for impartation of flame-retardancy to cotton fabric. The optimum add-on value of the mixture expressed in gram anhydrous additive per 100 g fabric was about 15%. The results obtained are in favour of gas theory and also in favour of chemical theory as well as condensed phase retardation.